Involuntary attrition in indian information technology firms (A) - Sohani, Shrihari S., (SAGE Knowledge. Cases., 2015)
Umang kept the copy of Times of India (TOI) down with a worry in his mind. He came to Bangalore in 2001 as an entry-level engineer in a multinational software firm and has remained with the same company, rising through the ranks to become a project manager. He was an expert in COBOL (for Mainframes), which had high demand when he joined the firm. Since the last couple of years, though, he has been noticing that with the advent of new technologies, customers were shifting their preference to newer applications that were more modular, less cumbersome and more easily configurable. COBOL-based applications were cumbersome but have been reliable till now. Of late, he also felt that the firm was paying more attention to engineers with newer skills such as cloud technologies, big data analytics, etc. and people like him were politely refused promotions and often kept away from new development focused projects. For the past 18 months, he has been working on a support project.